First American colonies - Oney, Yannick (New York Scholastic, 2004)
Explores how some of colonial North America's first towns were started and what life was like for the people who lived in them
Hurg
5
Keywords: United States -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature